GROUP EVENT RECOMMENDATIONS FRAMEWORK BASED ON DATA MINING - et. al., Lilly Sheeba S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Event recommendations square measure done solely to people and not for teams. This project aims to event recommendations for a gaggle of individuals. A gaggle event recommend system supported learning to rank technique has been projected. data {processing} may be a process utilized by firms to show information into helpful data. By victimisation software package to seem for patterns in massive batches of knowledge, businesses will learn additional concerning their customers to develop more practical promoting methods, increase sales and reduce prices. data processing depends on effective knowledge assortment, deposition and pc process. This project aims to event recommendations for a gaggle of individuals. a quick combine wise algorithmic program known as theorem cluster ranking is developed to find out ranking model for every cluster. it's not one algorithmic program however a family of algorithms wherever all of them share a typical principle, i.e., each combine of options being classified is freelance of every different. it's straightforward and straightforward to implement. It does not need the maximum amount coaching knowledge. It handles each continuous and distinct knowledge.